Absolute Study of Language Using Softskill Methodology - Rosida Tiurma Manurung (International Journal of Multi Discipline Science, 2018)
The aim of this paper is to do a research on study of language using soft skill methodology, because the supremacy of language is not solely master on concepts, theory, ideas, and etiquette of language, but the important thing is the supremacy of language that can be used as expansion character and personality. If this happen, people will supreme on language skill with expansion on character and high moral to dig the effectiveness. The need of skills are not technical. With soft skill, ones is able to have the circumstantial sensitivity, high creativity, that is able to look for unthinkable opportunity and gaps by others, conducting new concepts and innovative, and also can fulfill a new demand in society. Based study on soft skill methodology, it is expected to develop intelligence together with expansion character, sensitivity, personality, activity in social interaction, and high moral. The supremacy of language based on hard skill represents the old concepts and is out of date. The supremacy of language with soft skill methodology is absolute. In the discussion above, found the following things. In language learning, each teaching material is given special themes that can provoke soft skills of learners, in language learning in the classroom, there must be an interaction between lecturers and students, it is necessary to design tasks that empower soft skill skills to learners, with the soft skill approach, we can design the rules in the class, in language learning, soft skill approach can also be done in extra curricular and  to support language learning with soft skill approach, there are activities that can be used to develop soft skill.